Zagraniczna polityka kulturowa w Republice Federalnej Niemiec = Foreign cultural policy in the Federal Republic of Germany - Kruk, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Foreign cultural policy in the Federal Republic of Germany has a long tradition and establishes one of the pillar in foreign German policy. The aims of foreign German policy are various, from promotion of the knowledge of German language to action in direction of strengthen a positive German`s image outside of their borders.
Keywords: dyplomacja; zagraniczna polityka kulturowa; Niemiecka Republika Federalna